Effectiveness of a Paid Advertising Strategy on a Digital Platform to Increase Sales and Branding of SME Product - Isnaini - Nurkhayati; Azizah - Azizaha (Admisi dan Bisnis, 2023)
This study aims to look at the effectiveness of paid advertising on digital platforms that are currently commonly used by SMEs. Micro, small and medium enterprises (SMEs) are a business sector that has an important role in economic growth in Indonesia in general and in the city of Semarang in particular. Currently, SME actors have started to look at digital platforms as a marketing tool. So that consumers are familiar with the products sold by SMEs, intensive promotions need to be carried out. Placing advertisements on various digital platforms is important so that the product can be recognized by the wider community. Currently various digital platforms such as social media and marketplaces offer various types of paid advertising. Many SMEs are already interested in these various paid advertising features and are starting to use them to boost sales of their products. This study uses primary and secondary databases. The primary data used is obtained through direct observation in the field while running the business as well as information from the internal parties involved. Meanwhile, secondary data is obtained from the results of literature or documents from the internet, especially digital platform algorithms. Data collection was carried out using interview techniques with internal parties who made graphical observations of digital platform traffic data, as well as by implementing discussions with SMEs. For data from observations that were made indirectly, obtained through reports and analysis of advertisements on digital platforms used. brand awareness. All SMEs that carry out paid advertisements on digital media experience an increase in product sales, although the level of increase is not significant enough and is not always directly proportional to the funds spent and the duration of the advertisement.